La (des)construcción de la amada. Más sobre Camino de Ximena, de Santiago del Prado, y la Vita nuova, de Dante Alighieri - Wiesse Rebagliati, Jorge (2011)
One of the similarities that can be drawn between Dante’s Vita Nuova and Camino de Ximena (2002), Peruvian writer Santiago del Prado’s opera prima, has to do with its generic condition. As Dante’s Vita Nuova, in effect, del Prado’s Camino de Ximena can be labelled as a «trascendental autobiography». Another similarity can be advanced: the loved one’s status. This paper argues that both personae (Beatrice and Ximena) are different, even opposing characters. If one respects Dante’s mental frame, Beatrice is hyperreal, as she is a figura, in the terms specified by Eric Auerbach. Not so Ximena, if one is to respect Santiago del Prado’s frame of mind. Ximena must be imagined as a literary phantasy conceived by a cultivated artist.